2019
DOI: 10.1051/bsgf/2019011
|View full text |Cite
|
Sign up to set email alerts
|

Tectono-metamorphic evolution of shallow crustal levels within active volcanic arcs. Insights from the exhumed Basal Complex of Basse-Terre (Guadeloupe, French West Indies)

Abstract: In order to decipher the tectono-metamorphic evolution of shallow crustal levels of the active volcanic arc of the Guadeloupe archipelago (Lesser Antilles) we present new geochemical, geochronological, mineralogical and structural investigations of the so-called Basal Complex, the oldest and most eroded volcanic complex of Basse-Terre in Guadeloupe. Based on geochemical and mineralogical criteria we propose an updated geological map of this northern area of Basse-Terre. Using 40 Ar-39 Ar geochronology we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 106 publications
1
7
0
Order By: Relevance
“…The rocks of Dominica have been estimated to be not older than 7 mya (Bellon, 1988; Monjaret, 1985). Basse‐Terre of Guadeloupe has been estimated to be younger than 5 mya (Favier et al, 2019; Wadge, 1994). Most are K‐Ar dating estimates of the oldest surface rocks, which correlate with, yet outdate, the shield emergence and can hence lead to an underestimation of the true island ages (Obbard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The rocks of Dominica have been estimated to be not older than 7 mya (Bellon, 1988; Monjaret, 1985). Basse‐Terre of Guadeloupe has been estimated to be younger than 5 mya (Favier et al, 2019; Wadge, 1994). Most are K‐Ar dating estimates of the oldest surface rocks, which correlate with, yet outdate, the shield emergence and can hence lead to an underestimation of the true island ages (Obbard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally three metamorphic series with different P/T ratios have been identified from petro‐structural analysis of orogenic belts, and they are usually associated with different stages of evolution of a convergent margin (e.g., Ernst, 1976, 1977; Kornprobst, 2002; Spear, 1993; Yardley & Warren, 2020): Metamorphic series with high P/T ratios, deduced by regional scale distribution of dominant metamorphic imprints (e.g., Ernst, 1973; Miyashiro, 1961), are generally associated with Pressure‐Temperature (P‐T) conditions interpreted as peculiar of subduction and are referred to as Franciscan (or Sanbagawa) metamorphic sequences. Barrovian (or Dalradian) metamorphic series, which are characterized by intermediate P/T ratios, are traditionally interpreted as the effect of crustal thickening during continental collision both by mountain belt tectono‐metamorphic analyzes and by thermo‐mechanical modeling predictions (e.g., Barrow, 1912; Bohlen, 1987; England & Richardson, 1977; England & Thompson, 1984; Jamieson et al., 1998; Sandiford & Powell, 1991; Thompson, 1981; Thompson & England, 1984). Metamorphic facies series characterized by low P/T ratios (Abukuma or Buchan‐type metamorphism) have been generally associated with abnormally high geothermal gradients such as those of the island arc or ridge settings (Cloos, 1993; Fagan et al., 2001; Favier et al., 2019; Mevel et al., 1978; Oxburgh & Turcotte, 1970; Verati et al., 2018), slab rollback or increase of the slab dip after continental collision (Ji et al., 2019; Li et al., 2013; Menant et al., 2016; Schliffke et al., 2019; Sizova et al., 2019), post‐collisional extension (Carmignani & Kligfield, 1990; Vanderhaeghe, 2012), melt migration through the crust (Depine et al., 2008), local effects of contact metamorphism (Rothstein & Manning, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…Metamorphic facies series characterized by low P/T ratios (Abukuma or Buchan‐type metamorphism) have been generally associated with abnormally high geothermal gradients such as those of the island arc or ridge settings (Cloos, 1993; Fagan et al., 2001; Favier et al., 2019; Mevel et al., 1978; Oxburgh & Turcotte, 1970; Verati et al., 2018), slab rollback or increase of the slab dip after continental collision (Ji et al., 2019; Li et al., 2013; Menant et al., 2016; Schliffke et al., 2019; Sizova et al., 2019), post‐collisional extension (Carmignani & Kligfield, 1990; Vanderhaeghe, 2012), melt migration through the crust (Depine et al., 2008), local effects of contact metamorphism (Rothstein & Manning, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, along the Hikurangi margin (New Zealand) thermochronometry allowed determining rapid phases of magmatic thickening and burial (lasting 6 Myrs) followed by contrasting slow unroofing (lasting 40 Myrs) (e.g., Flowers et al., 2005). Along many volcanic arcs it has been demonstrated that active volcanoes were emplaced in their own metamorphosed magmatic basement that was promptly exhumed (Kuril: De Grave et al., 2016; Lesser Antilles: Favier et al., 2019). It is noteworthy that during arc migration, cooling of an arc pluton might be interpreted to record its exhumation, whereas it might be associated with a drop in the paleo‐geothermal gradient due to volcanic arc cessation (Kohút & Danišík, 2017).…”
Section: Introductionmentioning
confidence: 99%